Peran Guru Pendidikan Agama Islam Dalam Pembentukan Karakter Siswa SMAN 2 Sragen Tahun Pelajaran 2014/2015 - TOWAF AL FIKRI, ARWAN (2016)
Describe the purpose of this study on the role of Islamic religious education teachers in shaping the character of students SMAN 2 Sragen , as well as support and barriers faced . This research is a field research or field research located at SMAN 2 Sragen as a case study . The research method used is qualitative method narrative . The data used in this study were collected by using interviews , observation and documentation . After the data terumpul we analyze the data with the following steps : data reduction , data display , decision making and verification of data . Based on the results of the study showed: 1) The Role of Islamic Education Teachers in the Formation of Character Students at SMAN 2 Sragen include: Increasing the resources of Islamic religious education teachers, instructional Developing Islamic Education through religious activities, Forming part of Islamic Spirituality (Rohis), create an Islamic atmosphere School, Building a partnership with the community. 2) Support the formation of student character of the principal, the support of teachers, support of the students, support from parents or guardians of students, support from the community and support from alumni. 3) Barriers faced by Islamic religious education teachers in shaping the character of the students there are two factors: internal and external factors. constraints on internal factors include: limited allocation of instructional time, Tight schedule of activities, teacher of Islamic education only male, less caring attitude of some teachers towards religious activities in schools, lack of creativity of teachers in teaching methods. Barriers on external factors, among others: less support from parents or guardians of students in religious activities, negative influence negatively environment and Effect of technology and information